2017
DOI: 10.1080/23328940.2017.1384090
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol alters body temperature regulation in the female mouse

Abstract: Hot flushes are due to estrogen withdrawal and characterized by the episodic activation of heat dissipation effectors. Recent studies (in humans and rats) have implicated neurokinin 3 (NK) receptor signaling in the genesis of hot flushes. Although transgenic mice are increasingly used for biomedical research, there is limited information on how 17β-estradiol and NK receptor signaling alters thermoregulation in the mouse. In this study, a method was developed to measure tail skin temperature (T) using a small d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 71 publications
4
36
0
Order By: Relevance
“…A different group of GNX female mice was implanted with 17-ß estradiol (E2) pellets (0.5 mg/21 d). Similar to what has been previously reported, estrogen replacement caused an immediate mild reduction of T b in gonadectomized female mice [20]. Compared to placebo, estrogen lowered T b by 0.3-0.5°C during the active phase of the day and by~0.5°C during the inactive phase of the day (Figure 4(a) and Supplementary Table 1).…”
Section: -ß Estradiol Severely Reduced the Hypothermic Response To supporting
confidence: 86%
See 2 more Smart Citations
“…A different group of GNX female mice was implanted with 17-ß estradiol (E2) pellets (0.5 mg/21 d). Similar to what has been previously reported, estrogen replacement caused an immediate mild reduction of T b in gonadectomized female mice [20]. Compared to placebo, estrogen lowered T b by 0.3-0.5°C during the active phase of the day and by~0.5°C during the inactive phase of the day (Figure 4(a) and Supplementary Table 1).…”
Section: -ß Estradiol Severely Reduced the Hypothermic Response To supporting
confidence: 86%
“…Progesterone, estrogen, and androgen receptors have all been reported to be expressed in hypothalamic regions including the POA and to be able to influence T b [24][25][26][27][28][29]. Application of estradiol to the POA increased the firing rate of warm as well as some temperature-insensitive neurons and may contribute to explain of estradiol to lowers T b by increasing vasodilation and heat dissipation [20,30,31]; this reduction in T b is observed in our ad libitum data. Nevertheless, during CR, estradiol administration prevents T b reduction.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Telemetry data show 24-hour averages from the 2 telemetry sessions before and 3 weeks after tamoxifen or vehicle injections. Tail skin temperature was monitored every 5 min using a Nano-T temperature logger (Star-Oddi) that was attached to the ventral surface and 1 cm from the base of the tail in a 3D-printed polylactic acid collar modified from Krajewski-Hall et al(Krajewski-Hall et al 2018). Tail skin data show 24-hour averages for the same time periods as the telemetry data.…”
Section: Telemetry Recordingmentioning
confidence: 99%
“…Several studies have reported that estradiol (E 2 ) activates thermoregulatory mechanisms during exposure to heat in female rats [1][2][3][4][5]. Baker et al [1] demonstrated that, in the extreme heat of 38 °C, the increase in body temperature was greater in ovariectomized (OVX) rats than in OVX rats with E 2 replacement (OVX + E 2 ).…”
Section: Introductionmentioning
confidence: 99%